In vitro and in vivo antibacterial activities and phytochemical screening of 80% methanol extract from Ehretia cymosa leaves - Eshetu Mekonnen; Dumessa Edessa; Fitsum Weldegebreal; Abenezer Aklog; Tigist Gashaw (PLoS ONE, 2026)
Antibiotic resistance has emerged as one of the most urgent global health threats, undermining the effective treatment of bacterial infections. In response, scientific interest is increasingly focused on identifying natural and effective antimicrobial agents derived from medicinal plants. In Ethiopia, Ehretia cymosa ( E. cymosa ) is traditionally used to treat wound infections, fever, gastric ulcers, dysentery, and toothache. However, there is limited scientific evidence to support these traditional claims. Hence, the present study aimed to evaluate the in vitro and in vivo antibacterial activities and to screen the phytochemical profile of the 80% methanol extract of E. cymosa leaves. The air-dried and powdered leaves of E. cymosa were extracted using cold maceration with 80% methanol. The antibacterial activity of the crude extract was tested using the disk diffusion method against selected bacterial pathogens commonly associated with infections. An in vivo model of burn followed by infection was established in mice. Qualitative phytochemical screening was also performed. One-way analysis of variance followed by Tukey’s post hoc multiple tests was used to compare the means of all parameters. The leaves of E. cymosa demonstrated significant antibacterial activity (p < 0.001) against the tested bacterial strains in a dose-dependent manner compared with the control. The minimum inhibitory concentration ranged from 6.25 to 75 mg/mL, while the minimum bactericidal concentration against P. aeruginosa and E. coli was 200 mg/mL. In the in vivo model, the extract resulted in faster wound contraction and a shorter epithelialization period against S. aureus than against P. aeruginosa . The plant leaf is also rich in flavonoids, terpenoids, and tannins. The 80% methanol extract of E. cymosa leaves exhibited antibacterial activity in vitro and in vivo, which corroborates the traditional use of the leaves against infectious diseases. Further studies involving the isolation and characterization of the active compounds are recommended.